Biochemical and Histopathological Effects Induced by Methimazole in Rats Treated by vitamin C - Mohammed Hussein Hindi; Sabreen Majid Mohammed; Ali Husein Ali Al-Safar (University of Thi-Qar Journal of agricultural research, 2022)
In order to investigate some biochemical and histopathological changes effects of Methimazole (ME)in rats twenty-eight white female rats were equally divided into four target groups, (ME) The 1st group, was given sterile saline (0.9%) and served as a control (c). The 2nd group, was given Methimazole at dose 0.04 mg/kg B.W. orally (positive control). The 3rd group, was given Methimazole at dose 0.04 mg/kg B.W. and Vitamin C 200 mg/kg B.W. orally. The 4th group, was given only Vitamin C 200 mg/kg B.W. orally. Results aimed in the present study on the effect of Methimazole at daily intake doses to investigate possible adverse effects and modulate its possible mechanism by measuring the oxidant and antioxidant impact in brain and Ameliorative trail of vit. C. Vit C antioxidant, such as super oxide, increase super oxide elimination. examination revealed that the (ME) histopathological figures showed very small size thyroid gland that displayed atrophy, composed numerous small size follicles with normal follicular cells and C-cells. Study concludes, (vit c) can decreased thyroid damage caused by oxidative effects triggered by (ME) and linked to their antioxidant effects.